Fabrication and characterization of Al2O3 nanoparticle reinforced aluminium matrix composite via powder metallurgy - Norul Amierah, Nor Zamani; Iqbal, AKM Asif; Nuruzzaman, D. M. (Elsevier Ltd, 2019)
In this study, aluminium-aluminium oxide (Al-Al2O3) metal matrix nanocomposites (MMNCs) with the different volume content of Al2O3 reinforcement were prepared. Three different types Al- Al2O3 nanocomposite specimens comprise of 10%, 15% and 20% volume fractions of Al2O3 were fabricated using conventional powder metallurgy (PM) route and their microstructure and mechanical properties were determined. The samples were prepared under 200 kN compaction load and 630 °C sintering temperature. The correlation between microstructure and mechanical properties due to the inclusion of Al2O3 nanoparticles were investigated. The optical micrographs revealed that the Al2O3 nanoparticles are almost uniformly distributed in the Al matrix with good bonding between matrix and reinforcement. Moreover, the mechanical properties including hardness, tensile strength and compressive strength of the nanocomposite increase with increasing volume fraction of the reinforcement. However, the impact strength decreases once the Al2O3 nanoparticles increase in the composite.